The molecular and endocrine basis of flatfish metamorphosis - Power, Deborah (2014)
A significant component of aquaculture is the production of good quality larvae, and, in the case of flatfish, this is tied up with the change from a symmetric larva to an asymmetric juvenile. Despite the pioneering work carried out on the metamorphosis of the Japanese flounder (Paralichthys olivaceus) and summer flounder (Paralichthys dentatus), the underlying molecular basis of flatfish metamorphosis is still relatively poorly characterized. It is a thyroid hormone (TH) driven process, and the role of other hormones in the regulation of the process along with the interplay of abiotic factors are still relatively poorly characterized as is the extent of tissue and organ remodeling, which underlie the profound structural and functional modifications that accompany the larval/juvenile transition. The isolation of genes for hormones, receptors, binding proteins, and other accessory factors has provided powerful tools with which to pursue this question. The application of molecular methodologies such as candidate gene approaches and microarray analysis coupled to functional genomics has started to contribute to understanding the complexity of tissue and organ modifications that accompany flatfish metamorphosis. A better understanding of the biology of normal metamorphosis is essential to identify factors contributing to abnormal metamorphosis.